The bridesmaid - Lewis, Beverly, 1949- (Minneapolis, Minn. : Bethany House, 2012)
Twenty-seven-year-old Joanna Kurtz has made several trips to the altar, but never as a bride. The single young Amish woman is a closet writer with a longing to be published something practically unheard of in her Lancaster County, Pennsylvania community. Yet Joanna's stories aren't her only secret. She also has a beau who is courting her from afar, unbeknownst even to her sister, Cora, who, though younger, seems to have suitors to spare.
Keywords: Amish women -- Pennsylvania -- Lancaster County -- Fiction; Women authors -- Fiction; Amish farmers -- Indiana -- Fiction; Man-woman relationships -- Fiction; Christian fiction; Love stories